The AI Revolution in Healthcare: Can Artificial Intelligence Finally Reduce Your Clinic Waiting Time? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The experience of a long wait time in a clinic or hospital is a universal source of frustration. These delays signal a deeper issue of operational inefficien...
Keywords: Machine Learning; Diagnostics; Artificial Intelligence; Medical Ethics